PROJECT-BASED LEARNING INTEGRATED WITH SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) TO THE CRITICAL THINKING SKILLS OF STUDENTS IN ELEMENTARY SCHOOL - Wiratman, Arwan; Bungawati, Bungawati; Rahmadani, Ervi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
This research aims to explore the influence of Project-Based Learning (PBL) integrated with Science, Technology, Engineering, and Mathematics (STEM) on the critical thinking skills of elementary school students in thematic learning. A quantitative design with a pre-experimental one-group pretest-posttest design was used in this study. The collected data was collected using observation and tests. The data is collected and analyzed descriptively and inferentially using the SPSS Version 26 application. Data analysis begins with descriptive statistics, normality, and hypothesis tests. The results showed an influence of Project Based Learning integrated with Science, Technology, Engineering, and Math on the critical thinking skills of elementary school students. Through that learning, students' necessary thinking skills are provoked and trained so that students can define, formulate, argue, and also conclude in solving a problem.